Stent-assisted coiling using the Neuroform Atlas stent for treatment of aneurysms that recur after coil embolization - Dong, Linggen; Wang, Jiejun; Chen, Xiheng; Zhang, Longhui; Zhao, Zhiqiang; Peng, Qichen; Jin, Zeping; Wu, Jun; Lv, Ming; Liu, Peng (Frontiers in Neurology, 2022)
Objective: To evaluate the safety and efficacy of stent-assisted coiling (SAC) using the Neuroform Atlas stent for aneurysms that recur after coil embolization. Methods: We retrospectively reviewed patients who underwent SAC using the Neuroform Atlas stent to treat aneurysms that recurred after coil embolization from November 2020 to November 2021. Patient and aneurysm characteristics, procedural details, complications, and angiographic and clinical follow-up outcomes were recorded and analyzed. Results: Eleven patients with 11 recurrent aneurysms were included for analysis. Atlas stent deployment was successful in all cases. Angiography immediately after the SAC procedure and at last follow-up showed complete occlusion in 10 patients (90.9%) and a residual neck in one (9.1%). Mean angiographic and clinical follow-ups were 9.2 and 10 months, respectively. A single procedure-related complication occurred, mildly blurred vision in the left eye, which recovered completely. No permanent morbidity or mortality occurred. Conclusions: SAC using the Atlas stent to treat aneurysms that recur after coil embolization is safe and effective. Large-scale studies with long-term follow-up are warranted to confirm our results.